2023
DOI: 10.1155/2023/9680371
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Motor Imaginary Combined with Transcranial Direct Current Stimulation (tDCS) on Balance in Middle-Aged Women with High Fall Risk: A Double-Blind Randomized Controlled Trial

Abstract: Introduction. The risk of falling and its subsequent injuries increases with aging. Impaired balance and gait are important contributing factors to the increased risk of falling. A wide range of methods was examined to improve balance, but these interventions might produce small effects or be inapplicable for this population. The current study aimed at investigating the effect of motor imaginary (MI) training combined with transcranial direct current stimulation (tDCS) over the cerebellum on balance in middle-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…One study showed ( Ouzzani et al, 2016 ; Mozafaripour et al, 2023 ) that were significant improvement in both balance tests in the intervention group after intervention compared to the control group. Both static and dynamic balance improved significantly from the baseline values only in the intervention group and not in the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed ( Ouzzani et al, 2016 ; Mozafaripour et al, 2023 ) that were significant improvement in both balance tests in the intervention group after intervention compared to the control group. Both static and dynamic balance improved significantly from the baseline values only in the intervention group and not in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence from tDCS, the articles point out that from two to six sessions, positive effects are observed on postural balance and indirectly on the fall risk of the older adults ( Ehsani et al, 2017 ; Yosephi et al, 2018 ; Baharlouei et al, 2020 ; Schneider et al, 2021 ; Lo et al, 2023 ; Mozafaripour et al, 2023 ; Sayig-Keren et al, 2023 ). These are satisfactory evidence, as interventions directed at the musculoskeletal system indicate that 12 to 20 weeks of balance training are needed to reduce the fear of falling and improve dynamic balance indices in older adults at high risk of falling ( Judge et al, 1993 ; Lord and Castell, 1994 ; Gusi et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cerebellum receives input from various sensory systems and proprioceptive information from muscles and joints. It integrates this information to create a comprehensive representation of the position of body and movement in space [54]. Impotently, the cerebellum acts as a feedback control system.…”
Section: The Central Effect Of Cerebellum On the Balance Controlmentioning
confidence: 99%
“…Standing balance refers to the ability of the human body to automatically adjust and maintain a stable posture in a resting state. A degeneration of the musculoskeletal system, as well as neurological damage from stroke, can affect an individual's ability to balance [1,2]. Maintaining standing balance is a complex physiological process that involves the coordinated work of the nervous system, musculoskeletal system, and sensory system.…”
Section: Introductionmentioning
confidence: 99%